2021
DOI: 10.1136/jitc-2021-003521
|View full text |Cite|
|
Sign up to set email alerts
|

Immune cell and tumor cell-derived CXCL10 is indicative of immunotherapy response in metastatic melanoma

Abstract: A T cell-inflamed tumor microenvironment is characterized by the accumulation and local activation of CD8+ T cells and Bat3-lineage dendritic cells, which together are associated with clinical response to anti-programmed cell death protein 1 (anti-PD-1)-based immunotherapy. Preclinical models have demonstrated a crucial role for the chemokine CXCL10 in the recruitment of effector CD8+ T cells into the tumor site, and a chemokine gene signature is also seen in T cell-inflamed tumors from patients. However, the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
67
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 92 publications
(74 citation statements)
references
References 23 publications
6
67
0
1
Order By: Relevance
“…Chemokines are small, secreted proteins that mediate immune cell trafficking (19)(20)(21) and immune cell recruitment into tumors (22)(23)(24). In particular, the expression of the CXCR3 ligands CXCL9 and CXCL10 in the tumor microenvironment is required for the recruitment of CD8 + T cells into inflamed tumor tissues (25)(26)(27)(28). CD8 + T cells exposed to cognate antigens may also express CCL4 to recruit additional CD8 + T cells via CCR5 (29).…”
Section: Introductionmentioning
confidence: 99%
“…Chemokines are small, secreted proteins that mediate immune cell trafficking (19)(20)(21) and immune cell recruitment into tumors (22)(23)(24). In particular, the expression of the CXCR3 ligands CXCL9 and CXCL10 in the tumor microenvironment is required for the recruitment of CD8 + T cells into inflamed tumor tissues (25)(26)(27)(28). CD8 + T cells exposed to cognate antigens may also express CCL4 to recruit additional CD8 + T cells via CCR5 (29).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, we propose that CXCR3 ligands are clinically relevant to targeted therapies, particularly as CXCL9 expression is strongly induced in BRAFi-treated melanoma patients but return to baseline in relapsing patients, mirroring CD8 expression dynamics and the observations in our mouse models. Consistent with this, multiple studies have found that CXCR3 ligands are critical for the action of anti-PD1/PDL1 immune checkpoint therapies (22,23).…”
Section: Discussionmentioning
confidence: 55%
“…Chemokines CCL7 and CCL8 are also highly induced in senescent PDAC cells following EZH2 inhibition and bind to the same receptor as CCL2 (CCR2), suggesting they could also play a role in NK cell trafficking into PDAC. Other SASP chemokines such as CXCL9/10 that bind to CXCR3 and are associated with T cell recruitment and “hot” TMEs in other cancer settings 53,54,56,63 are necessary for CD8 + T cell recruitment into PDAC following therapy-induced senescence. Remarkably, in our system, combining increased cytotoxic NK and CD8 + T cell trafficking via SASP chemokines with the enhanced immunogenicity of senescent cells is sufficient to potentiate anti-tumor immune surveillance in PDAC even in the absence of immune checkpoint blockade.…”
Section: Discussionmentioning
confidence: 99%